2008
DOI: 10.1890/06-1605.1
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Seagrass Species Composition and Function Over Two Decades

Abstract: Changes in the species composition and structural characteristics of marine vegetated habitats in response to climate change or local anthropogenic impacts may alter their quality as habitat for associated fish and invertebrates. Summer densities and biomass of the eelgrass, Zostera marina, declined significantly between 1985 and 2004 in Bogue Sound, North Carolina, USA, within the present‐day zone of biogeographic overlap in the distribution of this subtidal temperate species and the intertidal subtropical se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 47 publications
2
50
0
Order By: Relevance
“…Seagrass meadows are a habitat considered to be at high risk from climate change through increased thermal stress, increased storm incidence and changes in freshwater flows (Short & Neckles 1999, Waycott et al 2007, Micheli et al 2008; in recent times they have been lost at an unprecedented rate from a variety of anthropogenic influences (Waycott et al 2009). Predictions of the influence of climate change scenarios on seagrass (Short & Neckles 1999, Harley et al 2006, Poloczanska et al 2007, Waycott et al 2007) are largely based on incidences of seagrass loss associated with extreme weather (Cardoso et al 2008, Micheli et al 2008 as reported in short-term experimental studies (Campbell et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seagrass meadows are a habitat considered to be at high risk from climate change through increased thermal stress, increased storm incidence and changes in freshwater flows (Short & Neckles 1999, Waycott et al 2007, Micheli et al 2008; in recent times they have been lost at an unprecedented rate from a variety of anthropogenic influences (Waycott et al 2009). Predictions of the influence of climate change scenarios on seagrass (Short & Neckles 1999, Harley et al 2006, Poloczanska et al 2007, Waycott et al 2007) are largely based on incidences of seagrass loss associated with extreme weather (Cardoso et al 2008, Micheli et al 2008 as reported in short-term experimental studies (Campbell et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Predictions of the influence of climate change scenarios on seagrass (Short & Neckles 1999, Harley et al 2006, Poloczanska et al 2007, Waycott et al 2007) are largely based on incidences of seagrass loss associated with extreme weather (Cardoso et al 2008, Micheli et al 2008 as reported in short-term experimental studies (Campbell et al 2006). Long-term studies directly measuring seagrass changes and how they are correlated with climate are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Further, more frequent summer heat waves where water temperatures reach 30°C are likely to trigger permanent phase change in shallow waters, which would prevent future recovery of eelgrass meadows (Carr et al 2012). Similar losses will occur in the Bogue Sound-Back Sound in North Carolina (USA) (Micheli et al 2008). Restored eelgrass meadows are also vulnerable (Tanner et al 2010;Carr et al 2012).…”
Section: A Warming Estuarymentioning
confidence: 99%
“…Similarly, continued coastal development threatens seagrasses communities worldwide (Orth et al 2005. Abundances have declined 29% globally since 1879 and for the last several decades seagrasses have been disappearing at a rate of 110 km 2 yr −1 (Lotze, Lenihan, and Bourque et al 2006;Micheli et al 2008;Waycott et al 2009;Hughes et al 2009). At current rates, 30-40% of world seagrasses and their associated ecosystem services could be lost in the next 100 years Hughes et al 2009).…”
mentioning
confidence: 99%
“…Similar to other well-flushed coastal sounds, nutrient levels remain relatively low in spite of recent development of the watershed (O'Connor et al 2009). There is some evidence that current nitrate concentrations exceed levels observed several decades ago (Micheli et al 2008), suggesting some deterioration in water quality, but the lack of longterm records leaves this trend inconclusive. In response to rising sea levels, rock sills have been installed in Bogue Sound marshes since 1998 (Currin et al 2008).…”
Section: Study Systemmentioning
confidence: 99%